Reversible Reduction of Apparent Diffusion Coefficient Values in Bilateral Internal Capsules in Transient Hypoglycemia–Induced Hemiparesis - Albayram, S.; Ozer, H.; Gokdemir, S.; Gulsen, F.; Kiziltan, G.; Kocer, N.; Islak, C. (American Journal of Neuroradiology, 2006)
SUMMARY: A woman aged 68 years who experienced recurrent right hemiparesis caused by hypoglycemia was admitted to our hospital. When she was experiencing a low level of glucose, diffusion-weighted MR imaging showed the presence of hyperintensity lesions in the bilateral internal capsule. Diffusion-weighted MR imaging has been infrequently performed in patients with hypoglycemia. We report the reversible hyperintensity lesions on diffusion-weighted MR imaging in a hypoglycemic period in a patient with reversible hemiparesis. A reduction of apparent diffusion coefficient in a hypoglycemic period was clearly shown.